El estado constitucional de derecho en la legislación ecuatoriana y la crisis de la función judicial en la actualidad. - Balarezo Maza Tiana Nicole (2025)
In 2008, a milestone was marked in the history of the Ecuadorian state; since the last Constitution that is still in force was enacted, Ecuador was declared a "constitutional state of law and social justice," a legal premise that encompasses several aspects, one of the most relevant being equity in administering justice through the pertinent jurisdictional bodies empowered by the Constitution and corresponding law, a situation which in recent times has lost significance and given way to a lack of credibility among the citizenry. The judiciary is one of the five branches of government established in the 2008 Constitution, tasked with ensuring legal certainty, compliance with the law, and dispensing justice according to rights; the importance of its independence, transparency, legality, impartiality, and effective judicial protection in resolving cases are crucial for both internal social development within the State and the perception we project internationally as a country that upholds this solemn declaration of a constitutional state of rights and social justice. Over the past decade, the role of the judiciary has been compromised, as evidenced by various scandals surrounding the actions of its officials, creating an atmosphere of institutional instability and lack of credibility among the citizenry regarding their performance as previously emphasized; this has brought with it dire consequences, the most significant being insecurity and high levels of violence in the Ecuadorian State. Given the above, this analysis is important to determine the causes and consequences of the current crisis in the Judiciary and how it contradicts the declaration set forth in the 2008 Constitution regarding the rule of law and social justice. This work focuses on a critical analysis based on doctrine, basic principles declared for the 6 functioning of the Judiciary and its procedural system, aiming to identify the causes and consequences of this unprecedented crisis in our country. The methodology to be applied in this research is descriptive and explanatory, as it is necessary to describe the social phenomenon by investigating literature, legal norms, and practical cases that have arisen in Ecuador on this topic; complemented by the explanatory approach, allowing me to establish cause and effect of the phenomenon studied, make connections, and conclude with the dogmatic and interpretative method of constitutional and legal norms, providing a response to the problem addressed. Keywords: Judiciary, Crisis, Rule of Law, Social Justice, Credibility, Legal Certainty.